StRemorin1.3 hampers Potato virus X TGBp1 ability to increase plasmodesmata permeability, but does not interfere with its silencing suppressor activity. Issue 9 (18th March 2014) - Perraki, Artemis; Binaghi, Maria; Mecchia, Martin A.; Gronnier, Julien; German-Retana, Sylvie; Mongrand, Sébastien; Bayer, Emmanuelle; Zelada, Alicia M.; Germain, Véronique
Abstract : The Triple Gene Block 1 (TGBp1) protein encoded by the Potato virus X is a multifunctional protein that acts as a suppressor of RNA silencing or facilitates the passage of virus from cell to cell by promoting the plasmodesmata opening. We previously showed that the membrane raft protein StRemorin1.3 is able to impair PVX infection. Here, we show that overexpressed StRemorin1.3 does not impair the silencing suppressor activity of TGBp1, but affects its ability to increase plasmodesmata permeability. A similar effect on plasmodesmata permeability was observed with other movement proteins, suggesting that REM is a general regulator of plasmodesmal size exclusion limit. These results add to our knowledge of the mechanisms underlying the StREM1.3 role in virus infection. Abstract : Remorin does not affect the silencing suppressor activity of TGBp1. Remorin interferes with TGBp1, Hc‐Pro and 30 K ability to open PD. Remorin overexpression restricts plasmodesmal permeability.